Anti-Porphyromonas gingivalis and Anti-Inflammatory Activities of A-Type Cranberry Proanthocyanidins - La, Vu Dang (American Society for Microbiology (ASM), 2010)
A-type cranberry proanthocyanidins (AC-PACs) have recently been reported to be beneficial for human health, especially urinary tract health. The effect of these proanthocyanidins on periodontitis, a destructive disease of tooth-supporting tissues, needs to be investigated. The purpose of this study was to investigate the effects of AC-PACs on various virulence determinants of Porphyromonas gingivalis as well as on the inflammatory response of oral epithelial cells stimulated by this periodontopathogen. We examined the effects of AC-PACs on P. gingivalis growth and biofilm formation, adherence to human oral epithelial cells and protein-coated surfaces, collagenase activity, and invasiveness. We also tested the ability of AC-PACs to modulate the P. gingivalis-induced inflammatory response by human oral epithelial cells. Our results showed that while AC-PACs neutralized all the virulence properties of P. gingivalis in a dose-dependent fashion, they did not interfere with growth. They also inhibited the secretion of interleukin-8 (IL-8) and chemokine (C-C motif) ligand 5 (CCL5) but did not affect the secretion of IL-6 by epithelial cells stimulated with P. gingivalis. This anti-inflammatory effect was associated with reduced activation of the nuclear factor-κB (NF-κB) p65 pathway. AC-PACs may be potentially valuable bioactive molecules for the development of new strategies to treat and prevent P. gingivalis-associated periodontal diseases.